IDENTIICATION OF THE Lr34 GENE FOR RESISTANCE TO LEAF RUST IN VARIETIES AND COLLECTION SAMPLES OF WINTER SOFT WHEAT FROM THE AGRICULTURAL RESEARCH CENTER “DONSKOY” - N. N. Vozhzhova (Вавиловский журнал генетики и селекции)
Nowadays one of the priorities in winter soft wheat breeding is to provide resistance to leaf diseases, and, in particular, to leaf rust as the most harmful of them. The gene for resistance to leaf rust, Lr34, provides resistance to wheat plants at the slow development. The use of this gene together with other genes for resistance to leaf rust will allow obtaining varieties and samples less susceptible to the disease. The purpose of this work was to identify the Lr34 gene in the  varieties and collection samples of winter soft wheat in the Agricultural Research Center “Donskoy” (ARC “Donskoy”), because its presence was suspected due to the introduction of the variety “Bezostaya 1” in hybridization of the 1960s, but the study of this gene in our collection has not been carried out yet. The article gives the results of the study of 646 samples of winter soft wheat (including 36 varieties of ARC “Donskoy” introduced in the State Register of Breeding Achievements of the Russian Federation and 8 varieties being tested in the State Variety Testing) and identiication of the Lr34 gene and its allelic state. The assessment of the allelic state of the Lr34 gene has been carried out with the help of the codominant marker csLV34 using the method of PCR. There have been identiied 238 samples with the Lr34 gene in the dominant allelic state. The varieties Nakhodka, Bonus, Konkurent, Aksiniya, Kazachka, Donskaya polukarlikovaya, Donskaya bezostaya, Izyuminka, Zernogradka 9, Zernogradka 10 and Zernogradka 11 developed in SSE “ARC “Donskoy” are recommended as a source of the Lr34 gene to breed winter soft wheat resistant to the diseases.